Digitization of Urban Heritage Preservation Practices for Vilnius City - Fomin, Vladislav (Information & Media, 2022)
For UNESCO Heritage site Vilnius City, urban heritage preservation (UHP) is an important task aimed at monitoring various risks associated with preservation of heritage valuables in urban heritage areas. Those valuables can be small and large, tangible and intangible: building façade, building doors, windows, roof elements, gates, panorama view on a heritage site, heights of the building, volumes of the building, etc. Risks to heritage valuables may vary from gradual and cumulative processes (such as age-related degradation) to sudden and catastrophic events (such as floods, fires, or armed conflict). There are also risks connected to the intentional or unintentional destruction of cultural heritage. Those usually are the cases of city infrastructure development and purposeful rebuilding of the heritage objects.
Keywords: Urban heritage preservation; Vilnius; digitazation